Projects and research for the Education improvement and the use of Technology in Engineering - Manuel Castro Gil; María José Albert Gómez; Clara Pérez Molina; Gabriel Díaz Orueta; Rosario Gil Ortego; Elio San Cristóbal Ruiz; Sergio Martín Gutiérrez; Mohamed Tawfik Abuelela; Alberto Pesquera Martín (Universitat Politècnica de València, 2013)
The characteristics of a changing environment and immersed in the knowledge society, demand from enterprises, organizations, universities and society in general, continuous adaptation. This adaptation has to be linked to innovation as a real need, giving a dynamic response to new demands, as a result of the need to improve their operation processes. And that also affects the teaching of Engineering and Electronics, as well as Lifelong learning and the impact on the company itself. Remote accessibility and mobility are an example of this, and represent an innovation in the teaching-learning process, and therefore, in training. The research project "Remote-labs access in Internet-based Performance-centred Learning Environment for currículum Support" is presented for the remote accessibility study. Whose objective is the definition and development of an infrastructure based on European telematics for the organization of currículum through practice based on remote laboratories (RIPLECS). The execution of innovative projects is required for the implementation of these learning systems, in order to examine the integration of mobile devices and their effects on student learning and capacity. A research project in the business environment is presented: "E-business Mobile Training - use of de mobile performance Support System for acquiring e-business Mangement Skills (EMTM)". Curricular programs should connect to the real world of work, identifying the skills that will be needed for future work. Finally, in this line is presented an innovative project, "Performance-centred Adaptative Aurriculum for Employment Needs (PAC)". These three projects are a practical contribution of technology to the world of learning and training, facing the 21st century European educational challenges, by innovative emerging technologies applied to learning.